Research Trends in Technology-Enhanced Language Learning: A Bibliometric Analysis - Nasution, Awal Kurnia Putra; Batubara, Muhammad Hasyimsyah (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
Using bibliometric methods allows a quantitative understanding of the growth of TELL, and analysis of topic trends provides insight into the evolution of research interests, including significant growth in topics such as "Deep Learning". Using the Scopus database, a search query was developed to limit the study to articles published in the last 10 years, from 2014 to 2023. Results show consistent growth in TELL research, peaking in 2022 with 88 publications. Analysis of publication distribution identified a global contribution, with the United States as the main contributor, followed by China and the Russian Federation. Dominant keywords, such as “Language Learning,” “Engineering Education,” and “Students,” highlight the primary focus of research on enhancing the language learning experience through technology. The relationships between findings highlight how developments in one area of research often trigger changes in other areas, creating a dynamic and interconnected learning ecosystem. In conclusion, this research confirms that TELL is a field that continues to develop, demonstrating the importance of technology integration in language learning, especially the use of mobile technology.